Satu Tahun Virus Corona: Analisis Pergerakan Harga Saham Bank Syariah di Lantai Bursa - Elmira Siska; Novi Puji Lestari; Mekar Meilisa Amalia (Jurnal Ilmiah Ekonomi Islam, 2021)
The Corona virus affects practically every industry, including banking. The purpose of current research is to examine the stock price movements of Sharia Banks listed on the Indonesia Stock Exchange: Bank Panin Dubai Syariah Tbk. (PNBS), Bank BTPN Syariah Tbk. (BTPS), and Bank BRI Syariah Tbk (BRIS) after the Covid-19 outbreak entered Indonesia and to test a significant difference in the share price of Sharia Banks for 1 year before and after Covid-19 outbreak entered Indonesia. A quantitative research with a descriptive-comparative approach was employed. This analysis used secondary data in term of daily time series on stock prices for period one year before and after the Covid-19 outbreak entered Indonesia. Statistical technique applied were descriptive statistical and testing hypothesis using the Paired Sample T-Test. The finding revealed that the stock price movements of PNBS, BTPS, and BRIS after the Covid-19 outbreak entered Indonesia tend to be stable and able to grow positively. The Paired Sample T-Test findings show that there are significant differences in the stock prices of PNBS, BTPS, and BRIS before and after Covid-19 outbreak entered Indonesia, where Sharia Banks’ share price was higher after Covid-19 outbreak in Indonesia